TXD222: Pattern, Form and Technique II / College of Creative Arts - UiTM, College of Creative Arts (2023)
Intro to Pattern, Form and Technique II allows the students to review the techniques of pattern drafting and machining. In addition to this, the introduction of dart and pattern manipulation show the progress from flat pattern to a three dimensional product. The pattern drafting of the ‘torso’ block is also introduced. Its aim is to increase the awareness, sensitivity and understanding the relationship of shapes and form when used in clothing or in furnishing. These will prepare the students for a broader view and perspective of making patterns and forms.